Dynamic Properties of Concrete Composite Panels under Eccentric Compression Loading Tests - MAGALHAES, Max De Castro; SILVA, Roberto Marcio da (Archives of Acoustics, 2015)
The main aim of this paper is to examine the variability of some dynamic properties of concrete composite panels to in-plane eccentric compression loads via static and dynamic impact testing. First, experimental tests were performed in order to obtain the dynamic and static properties of concrete composite panels. In-plane eccentric loads were statically applied to a couple of panels in ten uniform steps. For each step, dynamic impact testing was performed and the modal damping, peak amplitude and natural frequencies obtained. Second, a ‘hybrid’ model, based on the concepts of modal analysis and the Finite Element Method, was developed in order to obtain the natural frequencies and corresponding normal modes of the composite panels within the frequency range 0–200 Hz. For this model, an initial warp of the panel middle surface was incorporated into the formulation in order to represent the applied flexural moment provoked by the eccentric in-plane loads. The accuracy of the ‘hybrid’ model was verified by comparison with the experimental results. Third, comparison is made between predictions (using on the ‘hybrid’ model) and experimental results.